German Practice in international law, 2019 / [edited by] Stefan Talmon. - Talmon, Stefan (Cambridge University Press, 2022)
Customary international law is based on State practice. This book presents the international law practice of Germany, the world's fourth-largest economy and a powerhouse of the European Union. That practice makes an important contribution to the creation and development of customary international law. It is the first and only presentation in English of German practice in the field of international law. The 2019 volume also provides comprehensive coverage of Germany's membership of the United Nations Security Council. The book combines a case study approach, providing analysis and commentary on Germany's practice, with a classic digest of primary materials, including diplomatic correspondence, statements and court decisions. The book is an ideal complement to other compilations of international law practice and is an essential resource for scholars and practitioners of international law. It will also be of interest to scholars of international relations, politics and diplomatic studies.